Efektivitas Pembelajaran Pemograman Mikrokontroler Menggunakan Aplikasi Arduino IDE - Dioan Perdana Adfry; Mukhlidi Muskhir; Afdal Luthfi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
The purpose of this study is to increase students' knowledge and skills in learning microcontroller programming in the subject of microprocessor and microcontroller programming at SMK Negeri 1 Koto XI Tarusan. This research was carried out in class XI TAV at SMK Negeri 1 Koto XI Tarusan on the subject of microprocessor and microcontroller programming. Observations in class XI TAV at this vocational school show that there are still many students who do not fully understand the concept of microcontroller technology. In addition, students' responses to microcontroller material also showed a lack of interest, which was reflected in the lack of enthusiasm in following microprocessor and microcontroller programming lessons. This research was implemented through an experimental and control approach, with research subjects consisting of students of class XI TAV 1 and class TAV 2 at SMK Negeri 1 Koto XI Tarusan. Data collection in this research was carried out using a questionnaire as a test instrument. The selection of experimental and control classes was carried out randomly. The data obtained from this study were then analyzed through various methods, including validity, reliability, learning completeness, practicality, normality, homogeneity, t-test, and effect size tests. The results of the questionnaire data analysis showed a very high level of validity and reliability, student learning completeness reached an adequate level, the practicality of learning was considered very practical, while the results of the normality, homogeneity, t-test, and effect size tests showed significance and normal data distribution.